2016
DOI: 10.1159/000447404
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients with Advanced Non-Small Cell Lung Cancer Enrolled in Clinical Trials

Abstract: Background: Up-to-date oncological therapy has been accomplished through the results of clinical trials (CTs). We analyzed the overall survival (OS) of patients with non-small cell lung cancer (NSCLC) and its relation to CT enrollment. Methods: The study included 1,042 patients with advanced NSCLC treated at the Instituto Nacional de Cancerología. All patients received treatment according to the national and international guidelines. Data were collected from medical records. Patients were subgrouped on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
(40 reference statements)
0
30
0
Order By: Relevance
“…Treatment at low-accruing centers was associated with increased risk of death of 91% (HR, 1.91; 95% CI, 1.37-2.65) after adjustment for prognostic factors and 72% (HR, 1.72; 95% CI, 1.23-2.40) after RT compliance adjustment. Similarly, Arrieta et al 14 reported a retrospective review of 1,042 patients with NSCLC in Mexico treated from 2007 through 2014 and concluded that enrollment in a clinical trial was associated with better OS (HR, 0.47-0.74), independent of other confounders.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Treatment at low-accruing centers was associated with increased risk of death of 91% (HR, 1.91; 95% CI, 1.37-2.65) after adjustment for prognostic factors and 72% (HR, 1.72; 95% CI, 1.23-2.40) after RT compliance adjustment. Similarly, Arrieta et al 14 reported a retrospective review of 1,042 patients with NSCLC in Mexico treated from 2007 through 2014 and concluded that enrollment in a clinical trial was associated with better OS (HR, 0.47-0.74), independent of other confounders.…”
Section: Discussionmentioning
confidence: 97%
“…Although a previous systematic review concluded that enrollment in clinical trials was not associated with a survival benefit, 5 it did not account for potential confounders, including socioeconomic status, age, race, comorbidity, or treatment year. Since that review, modern studies have been published showing a survival benefit for patients enrolled in trials, [13][14][15] after adjusting for confounders. Similarly, we found a benefit for survival among patients enrolled in a trial.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma, squamous cell carcinoma and large cell carcinoma are the three common types of NSCLC (2,3). In patients with lung cancer, 85-90% of cases are diagnosed as NSCLC (4). Compared with small cell carcinoma, the growth of NSCLC is slower (2).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with small cell carcinoma, the growth of NSCLC is slower (2). The clinical symptoms of NSCLC include fever, chest pain, shortness of breath, coughing and bloody sputum (4,5). Clinically, NSCLC is typically treated with surgery, chemotherapy, radiotherapy, immunotherapy and combination therapy (6).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Oncology , Arrieta et al [3] provide a retrospective review of 1,042 non-small cell lung cancer patients in Mexico treated from January 2007 to December 2014 who were or were not enrolled in a clinical trial. In this interesting and well-documented analysis, enrollment in a clinical trial was associated with superior overall survival.…”
mentioning
confidence: 99%